3D-printing of elastic stenosis phantoms (Transactions on Additive Manufacturing Meets Medicine, 2020)
Minimally invasive endovascular interventions play an important role in clinical practice. The procedures are a versatile tool to physicians and are therefore also important for the development of devices and imaging systems, which leads to a high demand for preclinical evaluation. This work focuses on the feasibility of 3D-printing for vessel phantoms with user defined stenoses made of elastic materials.
Keywords: endovascular intervention; vessel phantoms